Expressive Utterances In The Psalms Of Old Testament: A Pragmatics Perspective - Wardani, Dyah Ayu Kusuma, Dr. Maryadi, MA (2016)
This research focuses on expressive utterances in the Psalms of Old Testament. This research has two major objectives (1) to identify the syntactic form of expressive utterances found in the Psalms of Old Testament and (2) to find out the intention of expressive utterances found in the Psalms of Old Testament. This research is descriptive qualitative research. The data in this research are all English utterances that support the occurrence of expressive utterances. The source of data is Psalms of Old Testament. The data are collected using existing or secondary data method. The steps of collecting data in this research are reading the Psalms of Old Testament, taking note on all utterances containing expressive speech act, and giving codes on each datum. Techniques of analyzing data are describing the syntactic form referring to the theory by Fowler (1983) and Brown (1984), and describing the intention of expressive utterances referring to the theory of expressive speech act of Yule (1996). The result of the research shows that (1) the syntactic forms of expressive utterances are: The syntactic form of expressive utterances found in the Psalms of Old Testament is divided into 4 and the distribution is: (1) Declarative Sentence, declarative sentence itself is divided into 4 types namely; (a) Simple Sentence 25 data (30.48%), (b) Compound Sentence 14 data (17.07%), (c) Complex Sentence 7 data (8.54%), and (d) Compound-Complex Sentence 23 data (28.05%), (2) Imperative Sentence, imperative sentence itself is also divided into 2 types namely; (a) Positive 7 data (8.54%) and (b) Negative 2 data (2.44%), (3) Interrogative Sentence 2 data (2.44%), and (4) Exclamation 2 data (2.44%) and (2) The intention of expressive utterances found in the psalms of old testament is divided into 3 and the distribution is: praising 45 data (54.9%), statement of pain 24 data (29.3%), and statement of gratitude 13 data (15.8%). Keywords : syntactic form, expressive utterances, and Psalms of Old Testament